THE COVIDIZATION OF ENGLISH LANGUAGE TEACHING: CONCEPTS, EXPERIENCES, INSIGHTS, AND REFLECTIONS OF ESL TEACHERS: Received: 17th May 2021; Revised: 11th August 2021, 07th December 2021, 30th December 2021; Accepted: 5th January 2022 - De Asis-Ricamora, Maria Sharron (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This phenomenological research describes the concepts, experiences, insights, and reflections of ESL teachers on the covidization of language teaching amid the COVID-19 outbreak. A total of 19 informants from both public and private institutions agreed to participate in this research. Results of the study show that concepts on covidization centralized on utilization of different teaching modalities, challenges, pedagogical changes, and effects of the pandemic in language education. Experiences were expressed as positive and negative encounters in teaching. Moreover, their insights lead to suggestions to utilize appropriate strategies and methodologies in teaching English, exposure to ICT training, capacity-building, management support, and emotional support Covidization the outbreak and visualized their deep desires to move forward and accept the challenges with a positive goal in mind.